DEVELOPMENT OF A GUIDED INQUIRY-BASED BIOLOGY MODULE FOR TEACHING THE HUMAN REPRODUCTIVE SYSTEM FOR GRADE XI STUDENTS AT SMA NEGERI 1 NA IX X - Dewi Triana; Harahap, Hasmi Syahputra; Khairul (International Journal of Cultural and Social Science, 2025)
This study aims to develop a guided inquiry-based biology learning module on the reproductive system material for grade XI SMA/MA. This research is a type of research and development (Research and Development or can also be called R&D). Research and Development (R&D) is one of the research models used to produce a specific product from a problem and test the effectiveness of the product. The results of product validation and trials indicate that the guided inquiry-based biology learning module on the reproductive system material for grade XI SMA/MA obtained qualifications with a validation level of "very suitable" to use and received positive responses from biology teachers and students. This was obtained based on the percentage of product validation and trials results. The percentage results obtained for each were material experts at 91%, media experts at 81%, teacher responses at 96%, and student responses at 86.2%.